The association between antenatal corticosteroid use in late-preterm and early-term pregnancy and nonreassuring fetal status - JiEun Park; JiKwon Park; HyunChul Jo; InAe Cho; JongChul Baek (IMR Press, 2021)
This study aimed to compare perinatal outcomes, including nonreassuring fetal status, according to antenatal corticosteroid therapy (ACT) use during late-preterm and early-term pregnancies. This was a retrospective cohort study of women with singleton pregnancies who were at risk of late-preterm (34-36+6 weeks) birth or early-term (37-38+6 weeks) scheduled cesarean section from August 2017-July 2019. ACT was administered until June 2018, after which a policy was implemented such that ACT was not used for pregnant women in the above circumstances. Women were grouped based on whether they delivered before or after the policy change and were subdivided into late-preterm birth and early-term scheduled cesarean section groups to reduce variations in newborn outcomes. Multivariable logistic regression was used to determine whether the use of antenatal corticosteroids increased the odds of perinatal outcomes. In total, 216 women (215 neonates, 1 stillborn) were included. In the late-preterm delivery group, the rate of nonreassuring fetal status was significantly higher in the antenatal corticosteroid group than in the non-corticosteroid group (33.3% vs 12.0%, P = 0.017). In the early-term delivery group, the rate was non-significantly higher in the antenatal corticosteroid use group (19.0% vs 6.3%, P = 0.091). In the multivariable logistic regression, ACT was associated with an increased risk of nonreassuring fetal status (P = 0.025) and a reduced incidence of transient tachypnea of the newborn (TTN) (P = 0.011). We determined for the first time that ACT in late-preterm and early-term pregnancy is associated with nonreassuring fetal status. Here, ACT in late-preterm and early-term pregnancy had no benefit beyond decreasing the TTN rate.